In situ reactivation of glycerol-inactivated coenzyme B12-dependent enzymes, glycerol dehydratase and diol dehydratase. - Honda, S (1980)
The catalytic properties of coenzyme B12-dependent glycerol dehydratase and diol dehydratase were studied in situ with Klebsiella pneumoniae cells permeabilized by toluene treatment, since the in situ enzymes approximate the in vivo conditions of the enzymes more closely than enzymes in cell-free extracts or cell homogenates. Both dehydratases in situ underwent rapid "suicidal" inactivation by glycerol during catalysis, as they do in vitro. The inactivated dehydratases in situ, however, were rapidly and continually reactivated by adenosine 5'-triphosphate (ATP) and Mn2+ in the presence of free adenosylcobalamin, although in cell-free extracts or in cell homogenates they could not be reactivated at all under the same reaction conditions. ATP was partially replaced by cytidine 5'-triphosphate or guanosine 5'-triphosphate but not by the beta, gamma-methylene analog of ATP in the in situ reactivation. Mn2+ was fully replaced by Mg2+ but only partially by Co2+. Hydroxocoblamin could not replace adenosylcobalamin in reactivation mixtures. The ability to reactivate the glycerol-inactivated dehydratases in situ was only seen in cells grown anaerobically in glycerol-containing media. This suggests that some factor(s) required for in situ reactivation is subject to induction by glycerol. Of the two possible mechanisms of in situ reactivation, i.e., the regeneration of adenosylcobalamin by Co-adenosylation of the bound inactivated coenzyme moiety (B12-adenosylation mechanism) and the displacement of the bound inactivated coenzyme moiety by free adenosyl-cobalamin (B12-exchange mechanism), the former seems very unlikely from the experimental results.